1998
DOI: 10.1016/s0168-6496(98)00007-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of root exudates and bacterial metabolic activity on conjugal gene transfer in the rhizosphere of a marsh plant

Abstract: Genetic exchange between bacteria in natural habitats is believed to be strongly influenced by availability of growth substrates and growth rate. To test this hypothesis, conjugal transfer of an RP4 derivative between Pseudomonas fluorescens and Serratia sp. was studied in a simple sand/plant microcosm and was related to availability of root exudates and bacterial metabolic activity. The presence of the plant (Echinochlora crusgalli) greatly stimulated transfer. Average transfer ratios (T/D·R) were 8.9×10−11 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 5 publications
(5 reference statements)
2
16
1
Order By: Relevance
“…The low number of isolated transconjugants did not allow us to draw conclusions about atrazine treatment and rhizosphere effects on the transfer frequency of pADP1::Tn5. However, it has already been shown for other catabolic genes that (1) the selective pressure exerted by the xenobiotic can enhance the survival and growth of transconjugants in soil,38, 39 and that (2) the rhizosphere can act as a hotspot for plasmid transfer 40–44. In addition, no effects of either atrazine treatment or rhizosphere were observed on the nature of the isolated transconjugants.…”
Section: Discussionmentioning
confidence: 99%
“…The low number of isolated transconjugants did not allow us to draw conclusions about atrazine treatment and rhizosphere effects on the transfer frequency of pADP1::Tn5. However, it has already been shown for other catabolic genes that (1) the selective pressure exerted by the xenobiotic can enhance the survival and growth of transconjugants in soil,38, 39 and that (2) the rhizosphere can act as a hotspot for plasmid transfer 40–44. In addition, no effects of either atrazine treatment or rhizosphere were observed on the nature of the isolated transconjugants.…”
Section: Discussionmentioning
confidence: 99%
“…There is empirical evidence (Lilley et al, 1996; Kroer et al, 1998; Normander et al, 1998; Hausner and Weurtz, 1999) that – at least for certain plasmid–bacteria combinations – the dependence of conjugation rate on nutrient concentration is not of the first-order Monod form (see Section 1) used in Simonsen et al (1990), but rather exhibiting more of a threshold dependence with little or no conjugation for low levels of nutrient concentration and a nearly constant maximum conjugation rate for intermediate and high levels. (However, see Turner, 2004 for an unusual example of a plasmid whose conjugation rate appears to decrease at high glucose concentrations.)…”
Section: Methodsmentioning
confidence: 99%
“…In our preliminary experiment using tetrazolium salt, sodium 3 0 -{1-[(phenylamino)-car-bonyl]-3,4-tetrazolium}-bis(4-methoxy-6-nitro)benzenesulfonic acid hydrate (XTT) [27,28], the electron transport system (ETS) activity of E. coli S17-1 (pBHR1) in CBY100 medium with EMPs was significantly higher than in CBY100 medium alone (data not shown). It has been suggested that bacterial metabolic activity correlates positively with the conjugal plasmid transfer frequency [3], so the increased ETS activity that was observed in CBY100 medium with EMPs might be a key mechanism in the high conjugal plasmid transfer in the flasks containing either M. aeruginosa or its EMPs. On the other hand, it is known that the amount of space available for bacteria to colonize, except for factors that enhance bacterial activity, is important for promoting conjugal gene transfer [29].…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the possibility that conjugal gene transfer can occur in the natural environment, transfer frequencies have been investigated in various terrestrial [1][2][3][4] and aquatic [5][6][7][8][9][10][11][12] environments. Conjugal gene transfer is an important mechanism of gene transfer between bacteria.…”
Section: Introductionmentioning
confidence: 99%